2020
DOI: 10.1002/ajh.26020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spleen size and splenectomy on outcomes of allogeneic hematopoietic cell transplantation for myelofibrosis: A retrospective analysis by the chronic malignancies working party on behalf of European society for blood and marrow transplantation (EBMT)

Abstract: The role of spleen size and splenectomy for the prediction of post‐allogeneic hematopoietic stem cell transplant (allo‐HCT) outcome in myelofibrosis remains under debate. In EBMT registry, we identified a cohort of 1195 myelofibrosis patients transplanted between 2000‐2017 after either fludarabine‐busulfan or fludarabine‐melphalan regimens. Overall, splenectomy was performed in 202 (16.9%) patients and its use decreased over time (28.3% in 2000‐2009 vs 14.1% in 2010‐2017 period). By multivariate analysis, sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 55 publications
5
47
0
Order By: Relevance
“…In conclusion, our study yielded reassuring results with regard to pretransplant splenectomy; this procedure did not preclude allo-HCT in patients with MF. Together with the results by Polverelli et al 16 these suggest that pretransplant splenectomy can be safely performed and appears beneficial in patients with a massive splenomegaly,…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In conclusion, our study yielded reassuring results with regard to pretransplant splenectomy; this procedure did not preclude allo-HCT in patients with MF. Together with the results by Polverelli et al 16 these suggest that pretransplant splenectomy can be safely performed and appears beneficial in patients with a massive splenomegaly,…”
Section: Discussionsupporting
confidence: 56%
“…15 In the current issue of the American Journal of Hematology, Polverelli et al showed that splenectomy was associated with a lower rate of non-relapse mortality but a higher relapse rate in MF patients, and with a better overall survival in those with a massive splenomegaly. 16 Besides, splenectomy per se can be hazardous in patients with MF because it is associated with a substantial risk of thrombosis, hemorrhage or infection. [17][18][19] Some researchers have speculated that this type of complication could delay or even preclude allo-HCT in patients for whom no other curative options exist.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a low risk of graft failure in patients who responded regarding spleen size to RUX prior to transplantation (6%) in comparison to RUX pretreated patients with no or lost spleen response prior to HSCT (15%), which highlights the role of spleen size regarding risk of graft failure in myelofibrosis patients [ 22 ]. This is further supported by 7% graft failure incidence of the non-RUX pretreated patients who had only a median spleen size of 8 cm at time of HSCT.…”
Section: Discussionmentioning
confidence: 98%
“…136 Similarly favorable outcome data have also been reported in patients receiving alternative donor grafts. 141 Unresolved issues with AHSCT in MF include the role of splenectomy, [142][143][144] involved field radiotherapy, 145,146 and use of JAK2 inhibitors before and after AHSCT. [147][148][149][150][151] recent publications have addressed the issue of pre-transplant management of splenomegaly in MF, including splenectomy, splenic irradiation and use of JAK2 inhibitors.…”
Section: Allogeneic Hematopoietic Stem Cell Transplant In Myelofibrosismentioning
confidence: 99%